2021
DOI: 10.3390/jcm10214914
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Receptor as a Promising Marker for Early Prediction of Outcome in COVID-19 Hospitalized Patients

Abstract: The Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, has rapidly spread to become a global pandemic, putting a strain on health care systems. SARS-CoV-2 infection may be associated with mild symptoms or, in severe cases, lead patients to the intensive care unit (ICU) or death. The critically ill patients suffer from acute respiratory distress syndrome (ARDS), sepsis, thrombotic complications and multiple organ failure. For optimization of hospital resources, several molecular markers and algorithms h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Our data corroborated with findings by Napolitano F et al wherein the authors suggest CKD as a significant risk factor for severity and mortality among ICU COVID-19 Patients [26]. Earlier studies have evaluated the role of suPAR in chronic dis-eases conditions, coronary artery disease severity [27], cardiovascular disease in chronic kidney disease [28] and others like diabetes, cancer and liver disease [22]. Azamet et al, 2020 suggested suPAR may be associated with pathophysiology of AKI in COVID-19 patients [29].…”
Section: Discussionsupporting
confidence: 92%
“…Our data corroborated with findings by Napolitano F et al wherein the authors suggest CKD as a significant risk factor for severity and mortality among ICU COVID-19 Patients [26]. Earlier studies have evaluated the role of suPAR in chronic dis-eases conditions, coronary artery disease severity [27], cardiovascular disease in chronic kidney disease [28] and others like diabetes, cancer and liver disease [22]. Azamet et al, 2020 suggested suPAR may be associated with pathophysiology of AKI in COVID-19 patients [29].…”
Section: Discussionsupporting
confidence: 92%
“… 9 Research so far has shown that the early identification of COVID‐19 individuals at low or high risk of serious illness may improve patient stratification, but, currently, admission blood biomarkers have only moderate predictive value for COVID‐19 outcome and decision making in the clinical setting. 10 suPAR seems extremely promising as a COVID‐19 prognostic marker and may assist in the early selection of patients who can be discharged and continue self‐isolation at home or must be admitted to the hospital and/or intensive care unit. 10 , 11 , 12 , 13 In order to investigate the prognostic ability of suPAR in COVID‐19, we designed the SPARCOL study to assess whether suPAR measured at hospital admission is associated with illness severity in adult patients hospitalized primarily for COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
“… 10 suPAR seems extremely promising as a COVID‐19 prognostic marker and may assist in the early selection of patients who can be discharged and continue self‐isolation at home or must be admitted to the hospital and/or intensive care unit. 10 , 11 , 12 , 13 In order to investigate the prognostic ability of suPAR in COVID‐19, we designed the SPARCOL study to assess whether suPAR measured at hospital admission is associated with illness severity in adult patients hospitalized primarily for COVID‐19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both full-length and cleaved forms of uPAR can be subjected to the cleavage of the GPI anchor. This further cut generates soluble forms of uPAR that circulate in the blood at a very low level, but its circulatory level is elevated in cancer and in diverse inflammatory conditions [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%